Short-term functional outcomes in patients undergoing primary total knee arthroplasty according to their body mass index - Oropeza-Bonfanti, Fabiola; Bobadilla-Lescano, Guillermo; Martinez-Escalante, Felipe; Vallejo-Gómez, Eduardo; Balam-May, Angel de Jesus; Camara-Arrigunaga, Felipe (International Journal of Research in Orthopaedics, 2024)
Background: The impact of an increased body mass index (BMI) in patients with ostheoarthritis who undergo total knee arthroplasty (TKA) remains a controversial variable in terms of risks and benefits. This study aimed to evaluate the influence of BMI in the functional outcomes of patients with ostheoarthritis who underwent TKA. Methods: We followed a cohort of patients who underwent total knee arthroplasty with a primary diagnosis of osteoarthritis. Patients were stratified into 3 groups according to the World Health Organization classification of BMI. We assessed the association between BMI group and functional scores using the Western Ontario and McMaster osteoarthritis index (WOMAC) over the time intervals of pre– and postoperatively at 1 month, 3 months and 1 year. Results: The difference in means between pre-surgical WOMAC and WOMAC at first follow-up according to each BMI group was divided as follows: normal 10.9 (p=0.195), overweight 15.7 (p≤0.001) and obese 20.6 (p≤0.001). Study participants with a higher BMI had worse preoperative WOMAC scores and had greater improvement from baseline to 1 month. After one year of follow-up, participants in all BMI groups had similar WOMAC scores. Conclusions: Patients with obesity who underwent TKA showed greater functional improvement one month after surgery compared to the other BMI groups. Subsequently, it was observed at the end of the 12-month follow-up that all patients, regardless of BMI, had improved functional outcomes, and the magnitude of improvement was similar in all BMI groups.